Pengaruh Lokasi Tumbuh terhadap Perbedaan Aktivitas Antioksidan Ekstrak Metanol Daging Buah Kepundung (Baccaurea racemosa (Reinw. ex Blume) Müll. Arg.) - Lina Permatasari; Diyani Aulia Rahmah (Sinteza, 2026)
Excessive exposure to free radicals can potentially trigger degenerative diseases in the body. Therefore, antioxidant compounds are required to inhibit free radical reactions. Several antioxidant compounds can be naturally obtained from plants. Kepundung fruit (Baccaurea racemosa (Reinw. ex Blume) Müll. Arg.) is one of the fruits reported to contain bioactive compounds with potential antioxidant properties. However, the study about the effect of different growing locations on the antioxidant activity of kepundung fruit pulp has never been conducted before. This study aimed to determine the influence of growing location on the antioxidant activity of kepundung fruit pulp from two regions, Lombok and Banyuwangi. Kepundung fruit samples from both locations were extracted with methanol p.a. using the maceration method. The antioxidant activity of each sample was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, with quercetin as the positive control. The IC₅₀ values of quercetin and the samples from both locations were analyzed using One-Way ANOVA with a significance level of P < 0.05.The results showed that the IC₅₀ values of the methanol extract of kepundung fruit pulp from Lombok (EMBKL) and Banyuwangi (EMBKB) were 387.53 ± 2.67 µg/mL and 425.17 ± 16.98 µg/mL, respectively. A lower IC₅₀ value indicates higher antioxidant activity; thus, the extract from Lombok exhibited greater antioxidant activity. However, statistical analysis revealed that the antioxidant activity values of the two samples were not significantly different. Therefore, the growing locations of both samples likely share similar environmental conditions.